Tuberculosis in Brazil: Epidemiological aspects, diagnosis, and treatment - Ramos, Lucas Gabriel Quadros; Silveira, Fernanda Moreira Soares Boaventura; Alves, Jessica Elen Martins; de Prince, Karina Andrade (Seven Editora, 2024)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, considering that this comorbidity represents a public health problem, it is of paramount importance to understand the associated clinical, epidemiological, and economic factors due to its high prevalence in Brazil. The objective of this study was to review the literature on the epidemiological aspects, risk factors, diagnosis, and treatment related to tuberculosis in Brazil. The bibliographic research was developed from the analysis of scientific articles, obtained from the VHL, National Library of Medicine and SCIELO databases. Tuberculosis is an infectious, chronic, granulomatous and necrotizing disease caused by the acid-fast bacillus. The most common form of presentation is pulmonary, and susceptibility to the disease is influenced by multiple factors: age, nutritional status, infection with the human immunodeficiency virus, habits and lifestyle, poor income and education, inadequate housing, population density, and fragility of systems. The best form of control is through early diagnosis. This diagnosis can be made through clinical, bacteriological, radiological and histopathological data. Sputum smear microscopy is performed using 2 to 3 samples collected in the morning in order to detect sputum smear microscopy patients. Culture in solid and/or liquid medium is used to evaluate the presence of mycobacteria and enable their identification. The standard therapy of the disease consists of the use of Rifampicin, Isoniazid Pyrazinamide and Ethambutol (RIPE) for 2 months and (IR) for 4 months. The effective implementation of prophylactic measures is essential to reduce the burden of tuberculosis in Brazil. This context highlights the need to strengthen tuberculosis control actions in all spheres of the health system, with a focus on early diagnosis, treatment adherence, and prophylaxis measures. DOI:https://doi.org/10.56238/sevened2024.018-053